Impact of MED12 mutation and CDK8 activity on uterine leiomyoma growth and response to gonadotropin-releasing hormone agonist treatment - Saki Tanioka; Ryoko Asano; Yukihide Ota; Koichi Nagai; Katsuya Takenaka; Taichi Mizushima; Yohei Miyagi; Etsuko Miyagi (PLoS ONE, 2026)
MED12 exon 2 mutation is the most frequent mutation associated with uterine leiomyomas. MED12 wild-type leiomyomas have a higher growth potential than mutant leiomyomas, suggesting that the mutation limits leiomyoma growth. MED12 forms a complex with CDK8 and is involved in the phosphorylation of RNA polymerase II, playing a role in transcriptional regulation. However, its mechanism of action in leiomyoma growth is not clear. We aimed to clarify the relationship between MED12 mutation status, response to gonadotropin-releasing hormone (GnRH) agonist treatment, and CDK8 activity in leiomyomas. We also examined the effects of CDK8 inhibitors on primary cultured uterine leiomyoma cells. We classified 44 surgically removed uterine leiomyomas into four groups according to GnRH agonist use and MED12 mutation status. CDK8 was co-immunoprecipitated from leiomyoma tissue extracts using MED12 antibody to test its kinase activity in vitro , and the amount of phosphorylated substrate was measured. Cell proliferation and apoptosis of primary cultured MED12 wild-type leiomyoma cells were evaluated in the presence of a CDK8 inhibitor and sex steroid hormones. Of the 44 leiomyomas tested, 11 MED12 wild-type leiomyomas without preoperative GnRH agonist treatment had significantly higher CDK8 activity than nine GnRH agonist-treated MED12 wild-type leiomyomas and 15 leiomyomas with MED12 mutations without GnRH agonist treatment. Treatment of primary cultured MED12 wild-type cells with CDK8 inhibitors significantly inhibited cell growth and increased apoptosis. MED12 wild-type leiomyoma cells without GnRH agonist treatment showed high CDK8 activity, and inhibition of CDK8 activity suppressed cell growth in vitro .